1999
DOI: 10.1152/ajpendo.1999.277.5.e890
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of skeletal muscle glycogen phosphorylase and PDH during maximal intermittent exercise

Abstract: The time course for the activation of glycogen phosphorylase (Phos) and pyruvate dehydrogenase (PDH) and their allosteric regulators was determined in human skeletal muscle during repeated bouts of maximal exercise. Six subjects completed three 30-s bouts of maximal isokinetic cycling separated by 4-min recovery periods. Muscle biopsies were taken at rest and at 6, 15, and 30 s of exercise during bouts 1 and 3. Phos was rapidly activated within the first 6 s of bout 1 from 12% at rest to 47% at 6 s. The activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
283
4
6

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 230 publications
(315 citation statements)
references
References 36 publications
22
283
4
6
Order By: Relevance
“…Whilst with moderate aerobic exercise the rate of glycogenolysis will be matched closely with glucose oxidation, the considerable amount of glucose-6-phosphate released from glycogenolysis in the early stages of the initial REHIT sprint is likely to pose a substantial challenge to the intramyocellular milieu. Although the glycolytic catabolism of glucose-6-phosphate results in a rapid accumulation of pyruvate, only a small fraction of this is immediately oxidised; most is instead converted to lactate (Parolin et al 1999), as evidenced by the large spike in plasma lactate concentration observed in our study. The strong reliance on glycolysis for ATP resynthesis will also result in a reduction in both intramyocellular and blood pH levels (Robergs et al 2004).…”
Section: A Crucial Role For Glycogen Depletion?mentioning
confidence: 46%
See 4 more Smart Citations
“…Whilst with moderate aerobic exercise the rate of glycogenolysis will be matched closely with glucose oxidation, the considerable amount of glucose-6-phosphate released from glycogenolysis in the early stages of the initial REHIT sprint is likely to pose a substantial challenge to the intramyocellular milieu. Although the glycolytic catabolism of glucose-6-phosphate results in a rapid accumulation of pyruvate, only a small fraction of this is immediately oxidised; most is instead converted to lactate (Parolin et al 1999), as evidenced by the large spike in plasma lactate concentration observed in our study. The strong reliance on glycolysis for ATP resynthesis will also result in a reduction in both intramyocellular and blood pH levels (Robergs et al 2004).…”
Section: A Crucial Role For Glycogen Depletion?mentioning
confidence: 46%
“…3-4 x 30 s) sprint efforts (Parolin et al 1999;Gibala et al 2009). This finding is supported by the data of Parolin et al (1999) who demonstrated that during three repeated 30-s all-out cycle sprints glycogen phosphorylase (and hence glycogenolysis) is predominantly activated during the first 15 s of the first sprint, and that further sprints break down little or no extra glycogen.…”
Section: A Crucial Role For Glycogen Depletion?mentioning
confidence: 99%
See 3 more Smart Citations